Climate Change Vulnerability Assessment for the Major Habitats and Species in Lung Ngoc Hoang Nature Reserve, Vietnamese Mekong Delta: 10.32526/ennrj/20/202200036 - Giao, Nguyen Thanh; Loi, Ly Van; Nhien, Huynh Thi Hong; Huy, Tran Ngoc (Environment and Natural Resources Journal, 2022)
The study assessed the vulnerability of habitats and species to climate change in Lung Ngoc Hoang Nature Reserve (NR), Vietnam. The vulnerability assessment tools for habitat and species were developed by the International Union for Conservation of Nature (IUCN). Community members, NR managers and experts in the fields of environment, economic and rural development were involved in this study. The results showed that saltwater intrusion and inundation could cause serious threats to habitats (i.e., open water, Lung, agricultural and Melaleuca habitats) and freshwater species. The combined impacts of drought and high temperature potentially increase forest fires for the Melaleuca habitat and decrease the quantity and quality of open water habitats. The Melaleuca and Lung habitats have a high baseline conservation status, in which Melaleuca habitats are more vulnerable than Lung habitats. Conversely, open water and agricultural habitats are at low baseline conservation status, but open water habitats are more vulnerable. In addition, the proliferation of invasive alien species, encroachment on agricultural cultivation, and the degradation of water quality are also great threats to the NR. Key species, including Melaleuca cajuputi, Elaeocarpus hygrophilus, Chitala ornate, Channa micropeltes, were at low threat of climate change. However, C. ornate and C. micropeltes are seriously endangered by seawater intrusion, drought and poor water quality. The findings of this study can provide essential information for NR managers to formulate water management plans for the protection and management of the habitats and species in Lung Ngoc Hoang NR.